Colloid cyst of the third ventricle: A clinical series of 19-cases - Bilgin, Emre; Cavus, Gokhan; Acik, Vedat; Arslan, Ali; Yalman, Celil; Ihsan Okten, Ali (Annals of Medical Research, 2021)
Aim: Colloid cysts are benign tumors originating from primitive neuroepithelial or endodermic origin in the third ventricle. Asymptomatic, as well as paroxysmal headache, gait disturbance, nausea, vomiting, learning difficulty and death may occur. Computed tomography (CT) is also seen as a round or oval, non-contrasting lesion. Magnetic resonance imaging (MRI) also shows hyperintense at T1 weighed and isointens at T2 weighed sequences. Stereotactic aspiration, microscopic or endoscopic approaches, shunt can be applied. Total excision should be targeted.Materials and Methods: We aimed to investigate the age, sex, complaint, hydrocephalus presence, neurological examination findings, surgical method and results of 19 cases of colloid cyst in our clinic between 2012-2017.Results: Eleven of 19 cases were female (57.9%) and 8 were male (42.1%).The average age was 27.2 (2-62). The most common complaint was headache. Ptosis due to visual disturbance was seen in 5.3% (1 patient), ataxia in 10.5% (2 patients), hydrocephalus with memory loss in 31.5% (6 patients). Six patients underwent cystectomy with endoscopic third ventriculostomy (ETV) and transcranial surgery in 13 patients. Ventriculoperitoneal shunt was performed to one patient at eight months after surgery. Rhinorrhea and menengitis was seen in one patient. Medical theraphy was given to this patient. One patient died because of acute cerebral anfarct.Conclusion: Asymptomatic old patients must be followed periodically. Symptomatic patients must be treated surgıcally and it must be combined by V-P shunt if patients had hydrocephalus. One of the surgıcal endoscopic or transcranial technique can be selected. Transcortical or interhemispheric techniques may be preferred to transcranial techniques.Keywords: Colloid Cyst; Total Resection; Hydrocephalus; Endoscopic Third Ventriculostomy.
Keywords: Colloid Cyst; Total Resection; Hydrocephalus; Endoscopic Third Ventriculostomy.